Corneal nerve fiber involvement in chronic inflammatory demyelinating polyneuropathy - KESKİNER ÖZTÜRK, EZGİ; AKKAYA TURHAN, SEMRA; TOKER, AYŞE EBRU; ULUÇ, KAYIHAN (My University, 2023)
BackgroundDespite the primary myelin-related pathophysiology, small fiber neuropathy (SFN) and axonal degeneration are also considered to be involved and associated with disabling symptoms and impaired quality of life in chronic inflammatory demyelinating polyneuropathy (CIDP). Demonstration of SFN usually requires complex or invasive investigations.ObjectsIn vivo corneal confocal microscopy (IVCCM) has evolved as a non-invasive, easily applied method for quantification of small fiber involvement in peripheral nerve disorders. We aimed to investigate the potential role of IVCCM in CIDP.MethodsIn this cross-sectional study, 15 patients with CIDP underwent assessment with clinical disability scales, neuropathic pain (NP) and autonomic symptom questionnaires, nerve conduction studies, and IVCCM. IVCCM parameters were analyzed and compared to those from 32 healthy controls.ResultsCorneal nerve fiber density (CNFD) and corneal nerve fiber length (CNFL) were significantly decreased in the CIDP group, compared to those in controls (p = 0.03 and p = 0.024, respectively). Langerhans cells and fiber tortuosity were increased in CIDP patients (p = 0.005 and p = 0.001, respectively). IVCCM parameters were significantly lower in patients with NP compared to those in patients without NP.ConclusionIVCCM shows promise as a non-invasive complementary biomarker in the assessment of demyelinating polyneuropathies, providing insights into the potential pathophysiology of these non-length-dependent neuropathies.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Neurology; Life Sciences; Health Sciences; Natural Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; Nöroloji (klinik); İnsan Bilgisayar Etkileşimi; Fizik Bilimleri; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Neurology (clinical); Human-Computer Interaction; Physical Sciences; Confocal confocal microscopy; Inflammatory polyneuropathy; Small fiber; Neuropathic pain; MARIE-TOOTH DISEASE; CONFOCAL MICROSCOPY; POLYRADICULONEUROPATHY REPORT; PERIPHERAL NEUROPATHY; SOCIETY GUIDELINE; DAMAGE; DIAGNOSIS; DYSFUNCTION; Corneal confocal microscopy; Infammatory polyneuropathy; Small fber; Neuropathic pain